Analytical Method Validation for UV Spectroscopic Assay Method of Trypsin-Chymotrypsin Tablets - Dinesh Singh; D. B. Joshi; R. S. Bhadauria (Journal of Biomedical and Pharmaceutical Research, 2023)
It is internationally recognized that validation is necessary in analytical laboratories. The use of validated methods is important for an analytical laboratory to show its qualification and competency. When analytical method is utilized to generate results about the characteristics of drug related samples it is essential that the results are trustworthy. They may be utilized as the basis for decisions relating to administering the drug to patients. Analytical method validation required during drug development and manufacturing and these analytical methods are fit for their intended purpose. The purpose of this validation is to show that processes involved in the analytical testing can be performed in an effective and reproducible manner. This article provides a good, complete, up-to-date collation of relevant information in the fields of analytical method validation of Trypsin-Chymotrypsin Tablets 50000 AU of Enzymatic Activity. Keywords: Analytical method validation, Pharmaceutical analysis, Specificity, Precision, Accuracy.